Assessment of Surface Preparation Methods for Mercury (Hg) Probe Schottky Capacitance-Voltage (MCV) on Epitaxial Silicon. (29th July 2021) - Sanna, Cristina; Taylor, Patrick; Hillard, Robert; Frey, Samuel; McDonald, Dan; Hoglund, Jonny; Zsakai, Gyula; Marton, Attila; Horvath, Peter
Abstract : Mercury probe (Hg-probe) Schottky capacitance-voltage (CV) is widely used for carrier density and resistivity profiling in silicon epitaxial layers. Preparation of the silicon surface is crucial for obtaining high-quality CV measurements. There are a variety of methods currently being used to treat bare silicon epitaxial and polished bulk surfaces in preparation for Hg-Schottky CV measurements. The treatments include wet chemical and dry treatments. Usually, the treatment can be the limiting factor for both the measurement time and quality. In this evaluation, a number of typical treatments are evaluated for P-Type Epitaxial silicon surfaces. A novel concept for treating surfaces has also been investigated, which involves placing a silicon wafer in a chamber where it is exposed to a thermal and optimized ambient. This pretreatment chamber is referred to as PTC. A physics-based assessment of the typical P-type silicon surface treatments is made and presented.